TOPICAL IMMUNOMODULATOR IN PROPHYLAXIS AND TREATMENT OF ACUTE RESPIRATORY INFECTIONS IN CHILDREN - V. V. Chernikov ("Paediatrician" Publishers LLC, 2012)
The bacterial lysates mechanism of action on the children immune system increasing the organism resistance against upper respiratory tract infections is described in this article. The authors represent a short review of safety and efficacy trials of the drug for acute respiratory diseases prophylaxis and treatment. The good tolerance of the drug was confirmed in all age groups. The therapeutic action of the drug consists of shortening of the disease duration and lowering of the acute respiratory infections domplications rate. Due to their immunomodulation effect it is reasonable to include the bacterial lysates into the treatment and rehabilitation of children with acute respiratory infections and other bronchial and lung diseases.